Risk Stratification And Outcome of Patients Presenting With Cellulitis - Ashish, Shukla; Chandreshekhar, Mahakalkar; Meenakshi, Yeola; KSHIRSAGAR, Shivani (International Journal of Psychosocial Rehabilitation, 2020)
Background: one of acute skin infection include cellulitis which usually occurs in immunocompromised population having visually indistinct borders majorly involves the dermis and subcutaneous tissue . its sign and symptoms includes erythema, edema, warmth, and tenderness, and usually occurs old age , diabetes mellitus, obesity etc Objectives : 1.To evaluate the risk factors associated with morbidity and mortality in patients with cellulitis 2. To analyze the outcome parameters in patients presented with cellulitis. 3. To compare outcome of patients with various treatment modalities. Methodology : This study will be conducted at AVBRH, Sawangi, Wardha, which is a tertiary care teaching hospital. The duration of the study will be 2 years from July 2019 to August 2021. The study will have the approval of the ethical committee of DMIMS, Sawangi, Wardha. In this study, patients of cellulitis admitted to casualty of AVBR Hospital will be studied prospectively my study design is prospective observational study . Study will be done in AVBR hospital sawangi in 2 years of duration ( September 2019 to august 2021) Inclusion criteria :Patients of any age with cellulitis ( that is infections that involve the skin and/or infection of subcutaneous tissue.)Exclusion Criteria –Patient presenting with myositis, Local complications, Diabetic foot infections. Average patient admition in our hospital in this duration will be 200000 if we take 95% as confidence level and 5% as margin of error population proportion 16% then my sample size comes as 207. So sample size is 210. Expected Results : During the study period cellulitis cases admit in AVBRH HOSPITAL it is expected that the male population with diagnosed or those ongoing treatment for diabetes mellitus will have a greater risk of developing cellulitis as compared to the female population with similar systemic disease. Conclusion : assessing the risk factors and eliminating the normal population will help in a targeted approach towards the screening, diagnosis and early treatment of cellulitis and will also help to prevent limb damage and tissue loss.